A microbiome abundant environment remodels the intestinal microbiota and improves resistance to obesity induced by chlorpyrifos in mice. (15th December 2022) - Li, Peize; Ma, Xiaoran; Liu, Donghui; Wei, Yimu; Li, Pengxi; Hou, Haonan; Yao, Jianing; Chen, Aisong; Liang, Yiran; Zhou, Zhiqiang; Wang, Peng
Abstract: There is a growing consensus that the appropriate microbiome abundant environment actuates microbiota changes to influence human health. Whether living environment reacts on the threat of contaminants and the underlying mechanism remain largely unknown. Therefore, we constructed microbiome abundant environment models, focusing on their regulatory effects on the obesity induced by the exogenous chemical chlorpyrifos (CPF) and the related mechanisms. The results uncovered that the constructed farm and woodland microbiome abundant environment could protect mice against CPF-induced obesity effectively. The microbiome abundant environment regulated CPF-induced microbiota imbalance, characterized by an increase in Lactobacillus abundance. These altered microbiotas modified the intestinal immune system by increasing the expression of Foxp3 and IL-10, and mitigated intestinal barrier injury by upregulating the expression of IL-22 and intestinal tight junction proteins. Fecal microbiota transplantation could receive similar phenotypes on alleviating CPF-induced obesity development. Our results demonstrate that the microbiome abundant environment attenuates exogenous chemical-induced health risks by remodeling the intestinal microbiota, improving the intestinal ecosystem, and preventing intestinal epithelial leakage. Graphical abstract: Image 1 Highlights: Soil exposure can affect intestinal microbiota and intestinal immune status in mice. Soil exposure can prevent the risk of obesity induced by chlorpyrifos (CPF). The remodeled gut microbiota protects on CPF -disrupted gut barrier functions. FMT can reduce the risk of obesity induced by CPF.